The Role of HF (Factor XII) in the Pathogenesis of the Thrombolytic State Induced by Venous Occlusion - Iatridis, S. G; Iatridis, P. G; Ferguson, J. H (Thrombosis and Haemostasis, 1966)
The effect of venous occlusion of the forearm on clotting and fibrinolysis was studied on 17 normal subjects. A post-occlusion increase in AHF (factor (VIII) and HF (factor XII) was noted. Fibrinolytic activity, as measured by euglobulin lysis time, plasma plate method, unheated fibrin plate method and plasminoplastin generation test, increased significantly in most of the subjects. A plasma lysokinase (indirect activator) seems to preponderate; this was also accompanied by some plasminoplastin (direct activator) activity. Low concentrations of ε-ACA and ATPase had an inhibitory effect upon the increased lytic activity. The data suggest that the post-occlusion lytic activity which was characterized to be of the lysokinase-type was intimately related to HF (factor XII).